The Financial Transparency Dynamics and Some Proposals on the Matter of Transparency Problem aimed at Developing Countries - Özker, Niyazi (Archives of Business Research, 2018)
In the study, we aimed to present some public budgetary dynamics that would have an impact on structural options in order to address some key structural issues such like transparency in particular developing countries with significant public deficits in the OECD. Transparency, as a financial phenomenon including to place in the objective of the budgeting, is to express the negative financial practices process that cause financial deviations for especially developing countries. Along with being monitored that some financial deflections related to financial transparency are inevitably appeared even after the developed financial formation process appearing from previous years to the current days. Namely, some measures and recommendations to transparency for especially developing countries in OECD countries to prevent central government budget deviations in practices are rather need to some more today's recommendations toward to both budget harmonization and optimal budget balances to present a comprehensive, accurate and reliable account of the public finances. It appears that this recommendations process mean also to identify, assess and manage prudently longer-term sustainability and other fiscal risks. It is understood that this recommendations process in the public budget process are rather meaningful also to identify, assess and manage prudently longer-term sustainability and other fiscal risks due to the fiscal plans and budgetary implementation through rigorous in the Central Budget Authority (CBE).